Data supporting 'Bioaugmentation of pilot-scale slow sand filters can achieve compliant levels for the micropollutant metaldehyde in a real water matrix' - Hassard, Francis; Jefferson, Bruce; Jarvis, Peter (Cranfield University, 2022)
Data for the manuscript titled: Bioaugmentation of pilot-scale slow sand filters can achieve compliant levels for the micropollutant metaldehyde in a real water matrix.
Keywords: bioaugmentation approach'; 'metaldehyde'; 'Pesticide'; 'Water Treatment'; 'Slow sand filters'; 'Environmental Engineering Design'; 'Water Treatment Processes'